2012
DOI: 10.1111/j.1478-3231.2012.02781.x
|View full text |Cite
|
Sign up to set email alerts
|

Controlled Attenuation Parameter (CAP): a noninvasive method for the detection of hepatic steatosis based on transient elastography

Abstract: The CAP is a promising tool for the noninvasive detection of hepatic steatosis. Advantages of CAP include its ease of measurement, operator-independence and simultaneous availability with LSM for fibrosis assessment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
259
1
5

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 306 publications
(280 citation statements)
references
References 36 publications
15
259
1
5
Order By: Relevance
“…For example, low vitamin D favours intrahepatic lipid accumulation due to increased circulation of free fatty acids (FFA), which is regulated via the J Gastrointestin Liver Dis, June 2016 Vol. 25 No 2: 175-181 peroxisome proliferator-activated receptor gamma (PPAR-γ) [12,13]. Although not all [14,15], many observational studies report associations between vitamin D deficiency and hepatic steatosis [12,16], the aggregate effect of which has been illustrated in a meta-analysis [17] confirming the presence of decreased serum 25-hydroxyvitamin D concentrations in such patients.…”
Section: Introductionmentioning
confidence: 73%
See 1 more Smart Citation
“…For example, low vitamin D favours intrahepatic lipid accumulation due to increased circulation of free fatty acids (FFA), which is regulated via the J Gastrointestin Liver Dis, June 2016 Vol. 25 No 2: 175-181 peroxisome proliferator-activated receptor gamma (PPAR-γ) [12,13]. Although not all [14,15], many observational studies report associations between vitamin D deficiency and hepatic steatosis [12,16], the aggregate effect of which has been illustrated in a meta-analysis [17] confirming the presence of decreased serum 25-hydroxyvitamin D concentrations in such patients.…”
Section: Introductionmentioning
confidence: 73%
“…We included patients with vitamin D deficiency (serum 25-hydroxyvitamin D < 20 ng/ml) [23] and significant liver fat accumulation, defined as a value ≥ 280 dB/m (as previously reported [24]) using controlled attenuation parameter (CAP) during transient elastography [25]. Exclusion criteria were based on a previously published study in which patients with chronic liver diseases received the same vitamin D supplementation regimen (for full details see [26]).…”
Section: Study Patientsmentioning
confidence: 99%
“…Moreover, CAP accurately detected > 10 and > 33% steatosis with AUROCs of 0.91 and 0.95, respectively [10]. A subsequent larger study of 153 patients with chronic liver disease and body mass index ≥ 28 kg/m 2 found that the optimum cut-off for detecting > 10% steatosis was 283 dB/m giving a sensitivity and specificity of 76 and 79%, respectively [11]. However, CAP had limited ability to differentiate between specific grades of steatosis, particularly between grades 2 and 3 [11].…”
Section: Controlled Attenuation Parametermentioning
confidence: 99%
“…A subsequent larger study of 153 patients with chronic liver disease and body mass index ≥ 28 kg/m 2 found that the optimum cut-off for detecting > 10% steatosis was 283 dB/m giving a sensitivity and specificity of 76 and 79%, respectively [11]. However, CAP had limited ability to differentiate between specific grades of steatosis, particularly between grades 2 and 3 [11]. The largest prospective study assessing CAP in NAFLD included 261 patients and explored the relationship between CAP and steatosis grade (S0 to S3) and also looked at discordance rates and factors associated with discordance [12].…”
Section: Controlled Attenuation Parametermentioning
confidence: 99%
“…hepatorenal index and evaluation of histogram of liver echogenicity differentiate stages of steatosis [4]. Fibroscan (Echosens, France) is widely used in Europe because it includes simultaneous liver stiffness measurement with transient elastography and assessment of steatosis with steatometry and controlled attenuation parameter (CaP) respectively [12]. CaP as a method is presented by correlation of stage of attenuation in liver parenchyma in dB/m with the stage of steatosis according to the morphological scale saF/Nas [14].…”
mentioning
confidence: 99%